Association between motor skills and executive functions in elementary school children.: Association between motor skills and executive functions - berahimi, elham; Askary, Reihaneh (Journal of Clinical Physiotherapy Research, 2025)
Introduction Motor skills and executive functions are key components in child development and affect cognitive and physical growth. Understanding how these skills are connected is important for children’s development. While previous studies have primarily focused on preschool-aged children, this study aims to investigate the correlation between motor skills and executive functions in elementary school children. Methods and Materials This study was a cross-sectional study with utilizing a descriptive-analytical approach. The sample consisted of 225 students from regular schools in Tehran, with an average age of 115/85 months. In this study, the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition short form (BOT-2 SF) was used to assess gross motor skills, fine motor skills, and upper limb coordination, while the Behavior Rating Inventory of Executive Function (BRIEF) was employed to evaluate students’ executive functions. Results The results indicate that motor skills (fine and gross motor skills) significantly correlate with executive functions in elementary students. Improving motor skills leads to better executive functioning, with bilateral coordination showing the strongest association (p < 0.001). Conclusion This study emphasizes the important relationship between motor skills, particularly bilateral coordination, and executive functions in elementary school children. It suggests that factors like age can affect how these skills are related. The results could help create customized educational and physical education programs that focus on the unique needs of each child, ultimately aiming to improve both their motor skills and executive functions simultaneously.